Playing the role: Power of love and love of power in Shakespeare's Twelfth Night - Matek, Ljubica (Anafora, 2022)
The author uses a methodological approach similar to one of New Historicism to give a new reading of Shakespeare’s comedy Twelfth Night, or What You Will. The play represents both a literary and a historical document which repeats the pattern of appropriating and exercising power used by Queen Elizabeth I. This reading reveals a new interpretative layer of Shakespeare’s seemingly apolitical comedy about mistaken identity and unrequited love which is resolved in a likewise seemingly typical happy ending that includes three marriages. A parallel analysis of text and context will show that Twelfth Night is a socially subversive text which points to the conclusion that masking seems to be a necessary prerequisite for achieving personal and political goals, both in the fictional context of the play and in the historical context of Elizabethan England.